A Rare and Intriguing Case of Wilson's Disease Initially Suspected of Systemic Lupus Erythematosus - Mandana Khodashahi; Najmeh Mohajeri; Moeid Reza Alipour; Reza Khademi; Nama Mohamadian Roshan; Behzad Aminzadeh; Muhammed Joghatayi (Clinical Case Reports)
ABSTRACT When systematic lupus erythematosus‐like lab results (e.g., positive anti‐double‐stranded DNA antibody, low complement component 3) are inconsistent with physical findings, such as the absence of arthritis or nephritis, clinicians should consider diagnoses such as Wilson's disease, especially in the presence of abnormal liver function and elevated international normalized ratio (INR).